2020
DOI: 10.3390/photonics7040095
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Broadband Optical Frequency Comb Based on a Gain-Switching 1550 nm Vertical-Cavity Surface-Emitting Laser under Optical Injection

Abstract: In this work, broadband optical frequency comb (OFC) generation by a gain-switching vertical-cavity surface-emitting laser (VCSEL) subject to optical injection is investigated experimentally. During implementing the experiment, a 1550 nm VCSEL under a large signal current modulation is driven into the gain-switching state with a broad noisy spectrum. By further introducing an optical injection, a high performance OFC can be produced. The experimental results demonstrate that the power and wavelength of the inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In 2020, Kim et al [26] found that conventional injection methods and injection processes like injection compression molding (ICM) are becoming more complex and harsher with high-speed injection at high mold and melt temperatures, with these approaches leading to a change in physical properties. In 2020, Ren et al [27], introducing optical injection, found that, under proper optical injection parameters, two sub-combs originating from two orthogonal polarization components of the VCSEL(vertical-cavity surface-emitting laser) can splice into a broadband total-OFC(optical frequency comb). In 2020, Huang et al [28] obtained results regarding optical-microscopy images and moldcavity pressure distributions which indicated that the weldline tensile strength and the interface compatibility between fibers and melts at the weldline region during the molding stage were higher in their use.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In 2020, Kim et al [26] found that conventional injection methods and injection processes like injection compression molding (ICM) are becoming more complex and harsher with high-speed injection at high mold and melt temperatures, with these approaches leading to a change in physical properties. In 2020, Ren et al [27], introducing optical injection, found that, under proper optical injection parameters, two sub-combs originating from two orthogonal polarization components of the VCSEL(vertical-cavity surface-emitting laser) can splice into a broadband total-OFC(optical frequency comb). In 2020, Huang et al [28] obtained results regarding optical-microscopy images and moldcavity pressure distributions which indicated that the weldline tensile strength and the interface compatibility between fibers and melts at the weldline region during the molding stage were higher in their use.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The semiconductors lasers employed for optical comb generation include the quantum cascade laser, [2][3][4] quantum dot lasers, 5,6 and Vertical-Cavity Surface-Emitting Lasers (VCSELs). 7,8 Most importantly, the rich nonlinear dynamics in semiconductor lasers [9][10][11][12][13][14][15] make them perfect candidates for optical comb generation. 16 In particular, VCSEL based-optical frequency comb has driven much attention recently due to its compactness, low energy consumption, possibility of integration, and mass production.…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely applied in arbitrary waveform generator 2,3 , optical metrology 4,5 , optical wavelength division multiplexing [6][7][8] , and other frontier fields. At present, OFC generation approaches mainly include laser mode locking technology 8 , micro ring resonance 9 , electro-optic modulator 10,11 , and gain-switching laser [12][13][14] . Especially, the scheme for generating OFC based on a gain-switching laser has received extensive attention due to the advantages of a relatively simple experimental system and easily tunable comb spacing.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 4 gives the optical spectra output from the square-current modulated VCSEL under optical injection with Vm-pp = 400 mV and different fm values, where 4(a)-(d) correspond to fm = 1.4 GHz, 1.8 GHz, 2.2 GHz, and 3.0 GHz, respectively. Since the variation of modulation frequency will cause the red shift of noise spectrum generated by current modulated VCSEL 12 , for different modulation frequency fm, it is necessary to select the matched injection wavelength so that the square-current modulated VCSEL after introducing optical injection can output OFC. For fm = 1.4 GHz and λi = 1555.893 nm, an uneven spectra structure can be observed in Fig.…”
Section: Introductionmentioning
confidence: 99%